La judiciarisation de l'action de la Confédération européenne des syndicats: Des affaires Viking et Laval à la défense des droits sociaux fondamentaux - Julien Louis (European Trade Union Institute (ETUI), 2022)
– This study examines the development and implementation of judicial strategies by the European Trade Union Confederation (ETUC) over the last fifteen years. Firstly, the author shows that this strategy was born in the wake of the Viking and Laval cases, with the aim of using the standards and complaint mechanisms of the Council of Europe and the International Labour Organisation to overturn those case laws. Secondly, the author highlights the normalisation and diversification of the objectives pursued by the ETUC's judicial strategy, as well as the limits of this strategy before the Court of Justice of the European Union. Finally, the author analyses the ETUC's activities in support of fundamental social rights in the Council of Europe before the European Court of Human Rights and the European Committee of Social Rights.
Keywords: 330; Internationale Arbeitsbeziehungen; Gewerkschaft; Strategie; Sozialstandards; Rechtsprechung; Standardisierung; EU-Recht